2013
DOI: 10.1111/j.1463-1318.2012.03172.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and short‐term effectiveness of EEA stapler vs PPH stapler in the treatment of degree III haemorrhoids: prospective randomized controlled trial

Abstract: Data suggest that the EEA stapler has better haemostatic properties than the PPH stapler and allows resection of a larger area of mucosal prolapse with potential benefits over the recurrence rate of haemorrhoid prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…Other possible reasons for an apparently higher incidence of prolapse after PPH such as persisting constipation or straining during defaecation might be relevant, but the finding of the study that the EEA achieves a more extensive mucosal resection and results in significantly fewer persistent haemorrhoid symptoms is likely to be significant. This is in addition to significantly less intraoperative and early postoperative anal bleeding, already demonstrated in our previous trial [9].…”
Section: Discussionsupporting
confidence: 74%
“…Other possible reasons for an apparently higher incidence of prolapse after PPH such as persisting constipation or straining during defaecation might be relevant, but the finding of the study that the EEA achieves a more extensive mucosal resection and results in significantly fewer persistent haemorrhoid symptoms is likely to be significant. This is in addition to significantly less intraoperative and early postoperative anal bleeding, already demonstrated in our previous trial [9].…”
Section: Discussionsupporting
confidence: 74%
“…Ng et al also reviewed 3711 patients using the PPH stapler and 4.3% of them had postoperative bleeding 19 . Using the DST stapler resulted in better intraoperative hemostasis than the PPH stapler in a randomized clinical trial, but the rate of postoperative bleeding was not statistically different 14 . In our practice, electrocauterization or sutures on the bleeders at the staple line were used for achieving hemostasis, which resulted in only one patient in the DST group with early postoperative bleeding in this study.…”
Section: Discussionmentioning
confidence: 84%
“…However, the majority of current studies have been focusing on the use of PPH stapler for hemorrhoidopexy, and comparison with the DST stapler has been rarely discussed. One randomized controlled trial that compared between the PPH stapler and the DST stapler reported that the DST stapler demonstrated a better hemostatic ability and allowed the resection of a larger area of mucosal prolapse 14 . However, that trial focused only on bleeding among the postoperative complications.…”
mentioning
confidence: 99%
“…Furthermore, the occurrence of serious complications such as rectovaginal fistulas, rectourethral fistulas, prostatic abscess, pelvic sepsis, persistent pain may have played a role in discouraging this technique [12,13]. As a consequence, some colorectal surgeons returned to the choice of traditional haemorrhoidectomy, and other modified the stapling technique using, for example the STARR technique with 2 PPH01 [20] or, more recently, the new high-volume circular staplers available in the market [21][22]. Others have adopted minimally invasive techniques such as DGHAL with mucopexy.…”
Section: Discussionmentioning
confidence: 99%